Efek Penggunaan Lahan Terhadap Degradasi Tanah Pada Kebun Campuran Di Kecamatan Kairatu Kabupaten Seram Bagian Barat Propinsi Maluku - Silwanus M Talakua; Rafael M Osok (Faculty of Agriculture, Pattimura University, 2018)
Land use is the most influential factor in soil degradation due to erosion. The objectives of this research are to know the level of land degradation and the factors that influence the land use area, the upper vegetation density and the lower vegetation density. This research uses the method of measuring ground damage indicator in the field. The results showed that single, wide land use, upper vegetation density and lower vegetation density had an effect on soil degradation on mixed garden land use; while simultaneously, wide land use, upper vegetation density and lower vegetation density have an effect on soil degradation on mixed garden land use. The most influential factors for soil degradation in mixed gardens are the area of land use and lower vegetation density.Keyword: Degradation of soil, land, vegetation density, mixed gardens.